Multi-Template Molecularly Imprinted Polymeric Electrochemical Biosensors - Meltem Agar; Maisem Laabei; Hannah S. Leese; Pedro Estrela (Chemosensors)
Dual- or multi-template molecularly imprinted polymers have been an attractive research field for many years as they allow simultaneous detection of more than one target with high selectivity and sensitivity by creating template-specific recognition sites for multiple targets on the same functional monomer. Dual/multi-template molecular imprinting techniques have been applied to identify, extract, and detect many targets, from heavy metal ions to viruses, by different methods, such as high-performance liquid chromatography (HPLC), liquid chromatography–mass spectrometry (LC-MS), and piezoelectric, optical, and electrochemical methods. This article focuses on electrochemical sensors based on dual/multi-template molecularly imprinted polymers detecting a wide range of targets by electrochemical methods. Furthermore, this work highlights the use of these sensors for point-of-care applications, their commercialization and their integration with microfluidic systems.